Analysis of The Effect of Seismic Load on The Design Safety Factor of Foam Mortar with Bored Pile Landslide Location of Batas Pidie/Aceh Besar – Bts. Kota Sigli STA 0+560 - Kurniawan, Ichvan Danny; Satrya, Trihanyndio Rendy; Aryani Soemitro, Ria Asih; Afzal, Fikri (Journal of Infrastructure & Facility Asset Management, 2025)
The Batas Pidie / Aceh Besar - Bts. Kota Sigli road section is a primary arterial road that has a very important role in connecting the capital city of Aceh Province with the capital city of North Sumatra Province. Landslide conditions that occur at the location of STA 0+560 can be caused by various factors, one of which is earthquakes. Aceh Province is a province with a high frequency of earthquakes. The design of foam mortar is simulated using the PLAXIS 2D auxiliary program to determine the stability of the slope against static load and seismic load. To determine the effect of seismic load on the safe number, the pseudostatic method of analysis and variation of seismic load with PGA of 0.4g, 0.45g, and 0.5g, 0.55g and 0.6g were used. From the results of the PLAXIS 2D modeling analysis on the reinforcement of slopes using foam mortar with a slope shows that the greater the seismic load PGA given, the value of the safe number will decrease, namely with a static load SF value of 1.932 (SF>1.5) and SF seismic load 0.4g of 1.285 (SF>1.1) to SF seismic load 0.6g of 1.121 (SF>1.1).